2019
DOI: 10.1371/journal.pone.0218125
|View full text |Cite
|
Sign up to set email alerts
|

A multi-targeting natural compound with growth inhibitory and anti-angiogenic properties re-sensitizes chemotherapy resistant cancer

Abstract: Targeted therapies have become the focus of much of the cancer therapy research conducted in the United States. While these therapies have made vast improvements in the treatment of cancer, their results have been somewhat disappointing due to acquired resistances, high cost, and limited populations of susceptible patients. As a result, targeted therapeutics are often combined with other targeted therapeutics or chemotherapies. Compounds which target more than one cancer related pathway are rare, but have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Likewise, there are several studies that report melanogenesis is suppressed as tyrosinase activity is inhibited by accelerating the proteasomal degradation of tyrosinase [ 33 , 43 ]. On the other hand, previous studies have shown that natural product (NP) compounds are capable of interacting with multiple cellular targets and targeting multiple signaling pathways, thus highlighting the potential of NP compounds as multi-target agents [ 27 , 44 , 45 , 46 ]. The ERK signaling pathway phosphorylates CREB and subsequently activates MITF to promote TYR, TRP1, and TRP2 transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, there are several studies that report melanogenesis is suppressed as tyrosinase activity is inhibited by accelerating the proteasomal degradation of tyrosinase [ 33 , 43 ]. On the other hand, previous studies have shown that natural product (NP) compounds are capable of interacting with multiple cellular targets and targeting multiple signaling pathways, thus highlighting the potential of NP compounds as multi-target agents [ 27 , 44 , 45 , 46 ]. The ERK signaling pathway phosphorylates CREB and subsequently activates MITF to promote TYR, TRP1, and TRP2 transcription.…”
Section: Resultsmentioning
confidence: 99%
“…Age-related diseases, including cancer, result from one or more failures at cellular and molecular levels, making difficult the identification of molecular targets for their prevention and treatment. Cancer prevention is an important theme for healthy aging and the role of the quality of one's diet for cancer prevention is definitely worthy of attention [34][35][36][37][38]. As for oral cancer, regarded as the main cause of death from oral diseases in many countries with the global estimates in 2018 of 354,864 new cases and 177,384 deaths, chemoprevention by dietary agents has evolved as a promising approach to control the incidence which has increased in many countries, especially in younger age groups [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…As for oral cancer, regarded as the main cause of death from oral diseases in many countries with the global estimates in 2018 of 354,864 new cases and 177,384 deaths, chemoprevention by dietary agents has evolved as a promising approach to control the incidence which has increased in many countries, especially in younger age groups [39,40]. The application of antioxidants or functional foods containing nutrients able to reverse or change epigenetic phenomena, makes nutrition a natural weapon to prevent cancer and improve health span [34][35][36][37][38]. In vitro evaluation of the anticancer effects of lactoferrin and tea polyphenol combination on Cal 27 cells showed a synergistic inhibition with induction of apoptosis and mitochondrial permeability transition [40].…”
Section: Discussionmentioning
confidence: 99%
“…Leukemia treatments include chemotherapy, radiation and targeted therapies, and stem cell transplants. However, the conventional therapies are limited by the associated high costs and anticancer drug toxicity, challenging researchers to develop biocompatible and cost-effective new drugs [5,6,7]. Recent findings have demonstrated the considerable potential of alternative interventions, such as immunotherapy and natural products (NPs), in the treatment of leukemia [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the conventional therapies are limited by the associated high costs and anticancer drug toxicity, challenging researchers to develop biocompatible and cost-effective new drugs [5,6,7]. Recent findings have demonstrated the considerable potential of alternative interventions, such as immunotherapy and natural products (NPs), in the treatment of leukemia [5,6,7]. NPs are capable of targeting multiple cancers and may provide a more robust treatment of cancer by limiting treatment-acquired resistance, increasing the efficacy of individual components in a cancer therapy cocktail, and reducing the associated side-effects to achieve a positive treatment response [5,6,7].…”
Section: Introductionmentioning
confidence: 99%